Behavioral Responses to Multisensory Stimulation in Preterm Infants - Kanagasabai, Parimala S.; Mohan, Divya; Lewis, Leslie E; Rao, Bhamini K. (Journal of Nepal Paediatric Society, 2016)
Background: Behavioral responses of preterm infant to sensory stimulation in the Neonatal Intensive Care Unit (NICU) are important to understand. This would enable NICU professionals to be cautious of overloading stimulations and ensure stability in preterm infants. The aim of this study was to describe the range of behavioral responses associated with multisensory (auditory, visual, tactile and vestibular) stimulation in preterm infants.Material and Methods: We recruited twenty-five preterm infants born at 28 to 36 weeks and birth weight of 1000 to 2000 grams for the study using convenience sampling. In the NICU, preterm infants from 32 weeks gestational age received multisensory stimulation session for duration of 12 minutes per day until discharge along with routine NICU care. During the stimulation, the behavioral responses of the preterm infants were observed and documented.Results: Limb activity and yawning were the most frequently observed behaviors. Sixty-five percent of the behavioral responses were observed during tactile stimulation. The frequency of observed behavioral responses decreased with successive stimulation sessions, which could indicate habituation responses in preterm infants to multisensory stimulation.Conclusions: Preterm infants showed behavioral responses indicating improved alertness and ability to integrate sensory stimulus. However, interpretation of preterm behaviors is a challenge because these behavioral responses could also indicate stress in preterm infants when coupled with other physiological and behavioral cues. Further studies are required to provide a detailed evidence for better clarity of infant’s responses to environmental stimuli.J Nepal Paediatr Soc 2016;36(2):110-114